High‐resolution cone‐beam computed tomography for assessment of bone invasion in oral cancer: Comparison with conventional computed tomography. Issue 10 (12th July 2017) - Czerwonka, Lukasz; Bissada, Eric; Goldstein, David P.; Wood, Robert E.; Lam, Ernest W.; Yu, Eugene; Lazinski, Dorothy; Irish, Jonathan C.
Abstract: Background: Radiologic assessment of mandibular bone invasion is critical in evaluating the extent of bone resection required in patients with oral cancer. There are a few reports of improved sensitivity with cone‐beam CT (CBCT) over conventional CT. Methods: A prospective cohort study of patients with oral squamous cell carcinomas adjacent to the mandible requiring marginal or segmental mandibular resection was performed. Patients were treated based on clinical assessment and conventional cross‐sectional imaging. Patients and surgeons were blinded to the results of CBCT performed preoperatively. Pathologic examination served as the gold standard. Results: Forty‐five patients were included in the study. Thirty‐three percent of the patients underwent segmental mandibulectomy and 37% had bone invasion. The sensitivity and specificity of CBCT were 91% and 60%, respectively, compared to 86% and 68% for CT with bone windows. Conclusion: A CBCT offers marginally improved sensitivity at the cost of reduced specificity for assessment of bone invasion compared to CT.